An unconventional family - Bem, Sandra L. (New Haven : Yale University Press, 1998)
"In 1965, when psychologists Sandra and Daryl Bem met and married, they were determined to function as truly egalitarian partners and to raise their children in accordance with gender-liberated, anti-homophobic, and sex-positive feminist ideals." "This book by Sandra Bem, an autobiographical account of the Bems' nearly thirty-year marriage, is both a personal history of the Bems' past and a social history of a key period in feminism's past. It is also a look into feminism's future, because the Bems' children, Emily and Jeremy, now in their early twenties, speak in the book as well."--Jacket
pt. 1. Coming together. Courtship. Why Daryl? -- pt. 2. Writing our own script. Community of family. Egalitarian partnering. Feminist child-rearing. My unorthodox career -- pt. 3. Evaluating our experiment. Egalitarian partnering revisited. Feminist child-rearing revisited.
Print version record.
English.
JSTOR
Keywords: Sex role; Families; Communication in families; Man-woman relationships; Feminism; Equality; Feminism; Gender Role; Rôle selon le sexe; Familles; Communication dans la famille; Relations entre hommes et femmes; Féminisme.; sex role; feminism; SOCIAL SCIENCE -- Gender Studies; Communication in families; Equality; Families; Feminism; Man-woman relationships; Sex role; Familie; Geschlechterrolle; Kommunikation; Sekseverschillen; Sekserol; Opvoedingsmethoden; Gezinsrelaties